FACTORS INFLUENCING LOYALTY TO TAOBAO MARKETPLACE FROM THE PERSPECTIVE OF CUSTOMERS FROM JIANGXI, CHINA - Xu Ling Na; Sujatha Balakrishna; Nur Hafizah Zainal; Nor Nazeranah Omar Din (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
This study looks at the variables affecting Chinese customers’ loyalty in online marketplaces. Global digitization has greatly aided the development of this online purchasing trend. The overarching objective of this research is to focus on the web of factors that shape Chinese consumers’ loyalty to online marketplaces. By unravelling the underlying variables and dynamics, this research aims to provide e-marketers with the tools and insights necessary to navigate the complexities of the Chinese market successfully. A quantitative analysis is employed to address the aim and objectives of this study. Survey questionnaire was utilized to gather data. The survey results underwent a rigorous examination with the aid of the Statistical Package for the Social Sciences (SPSS). Various statistical methodologies, including but not limited to multiple regression analysis to test hypotheses, the application of descriptive statistics to summarize data, and a comprehensive validity analysis, were employed in the process of scrutinizing and interpreting the survey findings. In conclusion, all four of the hypotheses established for the current inquiry are accepted with the help of hypothesis testing. The outcome of this investigation underscores the critical significance of various factors such as pricing strategies, the robustness of website security measures, the precision of information dissemination, and the influential role of word-of-mouth recommendations in shaping and sustaining consumer loyalty. The study’s findings serve as a compass for e-commerce entities, guiding them toward crafting more effective pricing strategies that resonate with their target audience. In sum, this research not only highlights on the dynamics of customer loyalty but also furnishes e-commerce businesses with actionable insights to elevate their customer retention strategies and brand marketing efforts.